COPD: what GPNs need to know from the latest GOLD update. (2nd April 2023) - Bostock, Beverley
Abstract : Every year, the Global Initiative for Obstructive Lung Disease publishes its update on COPD. Beverley Bostock provides an overview of what the latest publication means for general practice nurses The latest guidance from the Global Initiative for Obstructive Lung Disease (GOLD) on chronic obstructive pulmonary disease (COPD) will have an impact on the management of patients in general practice. The definition of COPD has been updated as well as the recommended approach to diagnosis. Updated treatment recommendations act as an important reminder for primary care clinicians to implement interventions that are relevant in the community setting and to refer on for more specialised interventions in secondary care as appropriate. The replacement of the ABCD assessment tool with the ABE approach underlines the significant impact that exacerbations can have in the management of COPD, independent of the symptom burden. Updated sections on exacerbations remind clinicians of the importance of considering comorbid or new diagnoses as the cause of any symptoms.